2008
DOI: 10.1111/j.1365-2702.2007.02130.x
|View full text |Cite
|
Sign up to set email alerts
|

The coping experiences of carers who live with someone who has schizophrenia

Abstract: Findings from this study demonstrate the importance of understanding the coping experiences of carers who have a family member with schizophrenia. Further research is needed to identify more important detailed factors that affect the coping strategies of carers. Relevance to clinical practice. Community mental health care professionals need to improve the quality of care for helping carers living with a family member who has schizophrenia. It is important to develop effective coping intervention strategies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
76
2
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(96 citation statements)
references
References 47 publications
(93 reference statements)
9
76
2
6
Order By: Relevance
“…"Coping mechanisms" refers to what a person does and thinks in response to an event or situation, thus dealing with events or situations with varying degrees of success (Huang, Sun, Yen, & Fu, 2008). Coping mechanisms can be viewed as positive or negative, either improving a person's wellbeing or being harmful to a person's wellbeing (Costa et al, 1991).…”
Section: Da Vid Publishing D Coping Mechanisms Of Caregivers Of Persomentioning
confidence: 99%
See 4 more Smart Citations
“…"Coping mechanisms" refers to what a person does and thinks in response to an event or situation, thus dealing with events or situations with varying degrees of success (Huang, Sun, Yen, & Fu, 2008). Coping mechanisms can be viewed as positive or negative, either improving a person's wellbeing or being harmful to a person's wellbeing (Costa et al, 1991).…”
Section: Da Vid Publishing D Coping Mechanisms Of Caregivers Of Persomentioning
confidence: 99%
“…Coping mechanisms are behavioural or cognitive responses made by any person contingent on a life event: thus coping is what a person does and thinks in response to an event, with varying degrees of success (Huang et al, 2008). This study hopes to highlight the variations in coping mechanisms used by caregivers in response to caring for family or community members who are severely mentally ill. Huang et al (2008) studied carers coping with those who suffer from schizophrenia in Taiwan and found that most carers were of low socio-economic status and low educational levels. This seemed to influence their COPING MECHANISMS OF CAREGIVERS OF PERSONS DIAGNOSED 618 coping mechanisms in that it delayed their seeking psychiatric help as they first went to traditional healers or tried Chinese medicine before going for psychiatric help (Huang et al, 2008).…”
Section: Da Vid Publishing D Coping Mechanisms Of Caregivers Of Persomentioning
confidence: 99%
See 3 more Smart Citations